Husband’s Support Towards Premenopouse’s Mother’s Anxiety Level In Facing Physical Changes In Sekarpuro Village, Ngadiopura Lor Dusun, Malang District - Welemina Yabar; Asruria Sani Fajriah (Journal of Health Science Community, 2026)
The purpose of this study was to determine the existence of husband’s support with the anxiety level of premenopausal mothers in dealing with physical changes in Sekarpuro Village, Ngadiopuro Lor Hamlet, Malang Regency. The study design was cross-sectional, with a population of 250 premenopausal women aged 40-55 years, and a sample of 72 respondents was obtained. By using purposive sampling technique. The questionnaire uses the Halminton rating scale for affinity (HRS-A) and the Liker scale. Data analysis used Spearman’s rank test. Most of the results (45.83) are between 40-50 years old; most (33.33%) of the respondents had elementary school education; most (55.56%) of the respondents have housewife jobs; most (59.7%) husband respondents support; most (54.2%) respondents experienced mild anxiety; and there is a relationship between husband’s support and the anxiety level of premenopausal mothers in Sekarpuro Village, Ngadiopuro Lor Hamlet, Malang Regency, with a value of p = (0.000) <(0.05). Future researchers are expected to involve husbands as respondents so that they know directly the husband’s support for premenopausal mothers.